2021
DOI: 10.1111/epi.16906
|View full text |Cite
|
Sign up to set email alerts
|

The molecular and phenotypic spectrum of CLCN4‐related epilepsy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…with a developmental and epileptic encephalopathy as highlighted in recent reports [1,11]. The severity of epilepsy, however, does not necessarily correlate with the severity of cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…with a developmental and epileptic encephalopathy as highlighted in recent reports [1,11]. The severity of epilepsy, however, does not necessarily correlate with the severity of cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%
“…Xu et al, reported on a female with ID, autistic features and brain abnormalities, with a maternally inherited CLCN4 missense variant where the mother had mild ID [ 8 ]. We recently summarized the published genotypic and phenotypic spectrum [ 9 ], noting that, to date, all CLCN4 variants studied in the Xenopus expression system demonstrated partial or complete loss-of-function (LOF) [ 1 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their function is not completely clear, but CLCN Cl − channels are involved in the regulation of excitability by controlling extra-and intracellular ion homeostasis. Dysfunction of some CLCN genes leads to severe neurological disorders, in particular LoF mutations in CLCN4 cause a spectrum of phenotypes including severe DEE with drug-resistant seizures, cognitive and behavioral disorders (494,495). SLC1A2 AND SLC6A1.…”
Section: Synaptic Transportersmentioning
confidence: 99%
“…These larger cohorts lead to a much better genotype–phenotype characterization of these syndromes. In the past 2 years, several single-center and multicentric studies have generated new insights into the electrographic and phenotypic spectrum of the following genetic epilepsies: PIGS-associated early-onset developmental and epileptic encephalopathy [6], Angelman syndrome [7], LAMA-2 -related muscular dystrophy [8], Mowat–Wilson syndrome [9], neurofibromatosis type 1 [10], CLCN4 -related epilepsy [11], Poirier–Bienvenu syndrome [12], and familial cortical myoclonic tremor with epilepsy type 1 [13].…”
Section: Genotype–phenotype Correlationmentioning
confidence: 99%